Configuring Load Balancing and Failover Using a Mikrotik Router on RT RW NET (Case Study: Dusun Klatakan Dayurejo) - Muhammad Muzayyin; Arif Senja Fitrani (Procedia of Engineering and Life Science, 2022)
The internet is something that is absolutely needed by every human being, as a result network administrators will implement various alternatives to meet user needs. The administrator will add an ISP line to be able to use the internet smoothly and easily. In fact, administrators often use an ISP's gateway line. This causes traffic inequality on the network when the number of users connected to the ISP line is much more. In the implementation of this final project, a load balancing and connection was made using 2 ISPs. The method used is the load balancing and failover method which is implemented using a mikrotik routerboard on the RT RW NET Dusun Klatakan network. With these two methods, all requests are based on the client that will enter the router that has been configured using the previous load balancing and failover method, so that the router will set the path based on the client through ISP 1 or ISP 2 in order to be able to back up each other's internet connections. The test results show the occurrence of equal access to access in a balanced way, so that there is no overload at one ISP.